Examining the Impact of Urban Morphology on Bicycle Mode Choice. (April 2014) - Rybarczyk, Greg; Wu, Changshan
Nonmotorized transport modes such as bicycling are becoming important components to urban transportation systems in the United States, in particular with the recent emphases on sustainable urban development. Recent bicycle forecasting methods have included urban design elements to help explain bicycle behavior but most measures lack accountability of microscale built form attributes that address bicyclist perception. This study developed a discrete choice model to examine the impact of urban morphological factors on people's utilitarian bicycle mode choice decisions. In the model, traditional factors considered include personal, household, and environmental variables. Urban morphology variables from space syntax were also incorporated in the model to test for the marginal influence of microscale design and space characteristics in the decision to bicycle. Results indicate that microscale built form factors that enhance visibility and contain well connected street networks significantly affected bicycle mode choice decisions at the trip origin. The finding that built form variables by and large influence the probability that someone will commute via bicycle suggests that policies and planning efforts aimed at increasing bicycle mode share should include human-scaled built form metrics that address urban space and cognition.